2017
DOI: 10.1021/acs.organomet.7b00304
|View full text |Cite
|
Sign up to set email alerts
|

Improved Synthetic Route to Heteroleptic Alkylphosphine Oxides

Abstract: A new method for the synthesis of heteroleptic alkylphosphine oxides (R 2 R 1 PO, where R ≠ R 1 ) from secondary phosphine oxides (or SPOs, R 2 HPO) is presented. These reactions were fast at room temperature, sterically selective, high yielding, and >95% pure after an aqueous wash. Deprotonation of an SPO generates a phosphinite anion ([R 2 P− O] − ) that was found to be highly selective for nucleophilic P−C bond formation (as opposed to O−C bond formation) with alkyl halides. Surprisingly, most strong orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
(56 reference statements)
0
14
1
Order By: Relevance
“…(Similar disubstituted products were also found in every other reaction of a phosphinite anion with 1-bromo-3-choropropane.) Substitution of the chloride is contrary to the observations in our previous study [32], which suggested little to no substitution would occur at the chloride position in the time it would take to substitute the bromide. The comparable rates of reaction observed in the current study may be due to the presence of the phosphonyl group near the alkyl chloride, which could stabilize the transition state by interacting with the Na + counterion (Figure 2A).…”
Section: Scheme 3 Reaction Of the Phosphinite Anion With 1-bromo-3-ccontrasting
confidence: 99%
See 4 more Smart Citations
“…(Similar disubstituted products were also found in every other reaction of a phosphinite anion with 1-bromo-3-choropropane.) Substitution of the chloride is contrary to the observations in our previous study [32], which suggested little to no substitution would occur at the chloride position in the time it would take to substitute the bromide. The comparable rates of reaction observed in the current study may be due to the presence of the phosphonyl group near the alkyl chloride, which could stabilize the transition state by interacting with the Na + counterion (Figure 2A).…”
Section: Scheme 3 Reaction Of the Phosphinite Anion With 1-bromo-3-ccontrasting
confidence: 99%
“…In prior work [32], we showed that the phosphinite anions displayed reactivity suggestive of an SN2-like mechanism, as indicated by their sensitivity to steric constraints and by their reactivity with alkyl halides following the trend RI > RBr > RCl. The observed regioselectivity allowed for isolation of (Me)2P(O)(CH2)3-5Cl species and subsequent reaction to form unsymmetrical bis(phosphine) oxides (Me)2P(O)(CH2)3-5P(O)(t-Bu)2 [32], Scheme 2. intermediates. In order to demonstrate the coordination chemistry of these ligands, two X-ray crystal structures of the metal complexes with unsymmetrical ligands were obtained.…”
Section: Scheme 1 Deprotonation and Subsequent Alkylation Of Spos Usmentioning
confidence: 80%
See 3 more Smart Citations